New species of Claustropyga Hippa, Vilkamaa & Mohrig (Diptera, Sciaridae) from the Holarctic region - Hippa, Heikki; Vilkamaa, Pekka (Zootaxa, 2016)
The following four new species are described: Claustropyga clavulata sp. n. (Canada), C. lobigera sp. n. (Finland), C. modica sp. n. (Finland) and C. stupenda sp. n. (Canada, Russia). A fifth, probably new species is briefly discussed. Claustropyga stupenda has spectacular morphological characters in its hypopygium. There are now 23 species in Claustropyga.